Interventions for preventing weight gain after smoking cessation. - Farley, A; Hajek, P; Lycett, D; Aveyard, P (2012)
BACKGROUND: Most people who stop smoking gain weight. There are some interventions that have been designed to reduce weight gain when stopping smoking. Some smoking cessation interventions may also limit weight gain although their effect on weight has not been reviewed. OBJECTIVES: To systematically review the effect of: (1) Interventions targeting post-cessation weight gain on weight change and smoking cessation.(2) Interventions designed to aid smoking cessation that may also plausibly affect weight on post-cessation weight change. SEARCH METHODS: Part 1 - We searched the Cochrane Tobacco Addiction Group's Specialized Register and CENTRAL in September 2011.Part 2 - In addition we searched the included studies in the following "parent" Cochrane reviews: nicotine replacement therapy (NRT), antidepressants, nicotine receptor partial agonists, cannabinoid type 1 receptor antagonists and exercise interventions for smoking cessation published in Issue 9, 2011 of the Cochrane Library. SELECTION CRITERIA: Part 1 - We included trials of interventions that were targeted at post-cessation weight gain and had measured weight at any follow up point and/or smoking cessation six or more months after quit day.Part 2 - We included trials that had been included in the selected parent Cochrane reviews if they had reported weight gain at any time point. DATA COLLECTION AND ANALYSIS: We extracted data on baseline characteristics of the study population, intervention, outcome and study quality. Change in weight was expressed as difference in weight change from baseline to follow up between trial arms and was reported in abstinent smokers only. Abstinence from smoking was expressed as a risk ratio (RR). We used the most rigorous definition of abstinence available in each trial. Where appropriate, we performed meta-analysis using the inverse variance method for weight and Mantel-Haenszel method for smoking using a fixed-effect model. MAIN RESULTS: Part 1: Some pharmacological interventions tested for limiting post cessation weight gain (PCWG) resulted in a significant reduction in WG at the end of treatment (dexfenfluramine (Mean difference (MD) -2.50 kg, 95% confidence interval (CI) -2.98 to -2.02, 1 study), phenylpropanolamine (MD -0.50 kg, 95% CI -0.80 to -0.20, N=3), naltrexone (MD -0.78 kg, 95% CI -1.52 to -0.05, N=2). There was no evidence that treatment reduced weight at 6 or 12 months (m). No pharmacological intervention significantly affected smoking cessation rates.Weight management education only was associated with no reduction in PCWG at end of treatment (6 or 12m). However these interventions significantly reduced abstinence at 12m (Risk ratio (RR) 0.66, 95% CI 0.48 to 0.90, N=2). Personalised weight management support reduced PCWG at 12m (MD -2.58 kg, 95% CI -5.11 to -0.05, N=2) and was not associated with a significant reduction of abstinence at 12m (RR 0.74, 95% CI 0.39 to 1.43, N=2). A very low calorie diet (VLCD) significantly reduced PCWG at end of treatment (MD -3.70 kg, 95% CI -4.82 to -2.58, N=1), but not significantly so at 12m (MD -1.30 kg, 95% CI -3.49 to 0.89, N=1). The VLCD increased chances of abstinence at 12m (RR 1.73, 95% CI 1.10 to 2.73, N=1). There was no evidence that cognitive behavioural therapy to allay concern about weight gain (CBT) reduced PCWG, but there was some evidence of increased PCWG at 6m (MD 0.74, 95% CI 0.24 to 1.24). It was associated with improved abstinence at 6m (RR 1.83, 95% CI 1.07 to 3.13, N=2) but not at 12m (RR 1.25, 95% CI 0.83 to 1.86, N=2). However, there was significant statistical heterogeneity.Part 2: We found no evidence that exercise interventions significantly reduced PCWG at end of treatment (MD -0.25 kg, 95% CI -0.78 to 0.29, N=4) however a significant reduction was found at 12m (MD -2.07 kg, 95% CI -3.78 to -0.36, N=3).Both bupropion and fluoxetine limited PCWG at the end of treatment (bupropion MD -1.12 kg, 95% CI -1.47 to -0.77, N=7) (fluoxetine MD -0.99 kg, 95% CI -1.36 to -0.61, N=2). There was no evidence that the effect persisted at 6m (bupropion MD -0.58 kg, 95% CI -2.16 to 1.00, N=4), (fluoxetine MD -0.01 kg, 95% CI -1.11 to 1.10, N=2) or 12m (bupropion MD -0.38 kg, 95% CI -2.00 to 1.24, N=4). There were no data on WG at 12m for fluoxetine.Overall, treatment with NRT attenuated PCWG at the end of treatment (MD -0.69 kg, 95% CI -0.88 to -0.51, N=19), with no strong evidence that the effect differed for the different forms of NRT. There was evidence of significant statistical heterogeneity caused by one study which reported a 4.3 kg reduction in PCWG due to NRT. With this study removed, the difference in weight change at end of treatment was -0.45 kg (95% CI -0.66 to -0.27, N=18). There was no evidence of an effect on PCWG at 12m (MD -0.42 kg, 95% CI -0.92 to 0.08, N=15).We found evidence that varenicline significantly reduced PCWG at end of treatment (MD -0.41 kg, 95% CI -0.63 to -0.19, N=11), but this effect was not maintained at 6 or 12m. Three studies compared the effect of bupropion to varenicline. Participants taking bupropion gained significantly less weight at the end of treatment (-0.51 kg (95% CI -0.93 to -0.09 kg), N=3). Direct comparison showed no significant difference in PCWG between varenicline and NRT. AUTHORS' CONCLUSIONS: Although some pharmacotherapies tested to limit PCWG show evidence of short-term success, other problems with them and the lack of data on long-term efficacy limits their use. Weight management education only, is not effective and may reduce abstinence. Personalised weight management support may be effective and not reduce abstinence, but there are too few data to be sure. One study showed a VLCD increased abstinence but did not prevent WG in the longer term. CBT to accept WG did not limit PCWG and may not promote abstinence in the long term. Exercise interventions significantly reduced weight in the long term, but not the short term. More studies are needed to clarify whether this is an effect of treatment or a chance finding. Bupropion, fluoxetine, NRT and varenicline reduce PCWG while using the medication. Although this effect was not maintained one year after stopping smoking, the evidence is insufficient to exclude a modest long-term effect. The data are not sufficient to make strong clinical recommendations for effective programmes to prevent weight gain after cessation.